Darkly dreaming Dexter : a novel - Lindsay, Jeff (New York : Vintage Books, 2009)
Dexter Morgan, who hides a secret life as an assassin while working as a murder analyst for the Miami police, is intrigued by the work of a new serial killer whose style mimics his own.
Keywords: Forensic scientists -- Fiction; Psychological fiction